Analysis of Doctor-Patient Relationship in Post-COVID-19 Period: Perspective Differences Between Citizen and Medical Staff - Lingmin Hu; Lijing Bai; Shenyu Zhao; Renjie Lu (SAGE Publishing, 2021)
To evaluate the current views on doctor-patient relationship (DPR) between citizens and medical staff in post-Corona Virus Disease 2019 (COVID-19) period and predict the possible factors of DPR, we distributed questionnaires by a online questionnaire platform--Questionnaire Star (https://www.wjx.cn) to evaluate DPR in post-COVID-19 period. Overall, 312 questionnaires for citizens and 421 questionnaires for medical staff were completed. Citizens felt that service attitude and communication with medical staff, and registering process have been improved. And their trust in doctors has increased by 86.8%. Majority of citizens (66.0%) preferred the tertiary hospitals. If doctor-patient contradictions occurred, 62.9% citizens preferred internal negotiation (with the doctor involved, 44.6%; with hospital management department, 18.3%). There was significant difference of views on the causes of medical violence incidents and the reasons for doctor-patient conflicts in the future between citizens and medical staff. The DPR score of medical staff was lower than citizens at each stage, and even showed a downward tendency in post-COVID-19 period. Furthermore, 20.4% medical staff believed that harmonious DPR would not be maintained, which was distinct from that of the citizens. Combating the COVID-19 provided an important opportunity to improve the DPR. However, unbalanced allocation of high-quality medical resources, gap between the actual treatment efficacy and patient's expectation, fairness and efficiency issues, financial conflicts, and medical information symmetry were still the influencing factors of DPR.